2018
DOI: 10.1101/492595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chikungunya virus outbreak in the Amazon region: replacement of the Asian genotype by an ECSA lineage

Abstract: 48 49 50 51 52 Corresponding authors: luiz.alcantara@ioc.fiocruz.br and nuno.faria@zoo.ox.ac.uk 3 53 Abstract 54 Background 55 Since its first detection in the Caribbean in late 2013, chikungunya virus (CHIKV) has 56 affected 51 countries in the Americas. The CHIKV epidemic in the Americas was 57 caused by the CHIKV-Asian genotype. In August 2014, local transmission of the 58 CHIKV-Asian genotype was detected in the Brazilian Amazon region. However, a 59 distinct lineage, the CHIKV-East-Central-South-America (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…Although evidence of cross-border transmissions among locations that share a tropical climate is frequent and has been observed previously in the region, for example, for DENV serotype 4 (Nunes, 2012) and CHIKV (Naveca et al, 2019), and although our results show that one isolate from Venezuela, a country with a high suitability for Ae. aegypti that has direct river connections to Manaus, clusters within the Manaus clade (Figure 5), we cannot exclude that some of the ZIKV introductions to Manaus were from Venezuela, therefore we cannot make speculations about the direction of the transmissions between the two countries, because of the lack of epidemiological data linked to this sample as well as a larger samples number from Venezuela.…”
Section: Discussionsupporting
confidence: 49%
“…Although evidence of cross-border transmissions among locations that share a tropical climate is frequent and has been observed previously in the region, for example, for DENV serotype 4 (Nunes, 2012) and CHIKV (Naveca et al, 2019), and although our results show that one isolate from Venezuela, a country with a high suitability for Ae. aegypti that has direct river connections to Manaus, clusters within the Manaus clade (Figure 5), we cannot exclude that some of the ZIKV introductions to Manaus were from Venezuela, therefore we cannot make speculations about the direction of the transmissions between the two countries, because of the lack of epidemiological data linked to this sample as well as a larger samples number from Venezuela.…”
Section: Discussionsupporting
confidence: 49%
“…In this study, we increased the number of CHIKV genomes deposited in the NCBI by generating 422 genomes that cover 12 Brazilian states over the years 2021-2022. By combining genomic and demographic data this effort has provided a comprehensive overview of CHIKV ECSA phylogeny in Brazil which summarizes and updates previous phylogenies from other studies of localized outbreaks 10,12,14,26,27 . The updated and metadataenriched dataset allowed us not only to describe the genetic diversity of circulating CHIKV variants but also to describe branching patterns observed in the updated phylogeny and infer the divergence time and likely location of emerging distinct subclades from the Brazilian lineage.…”
Section: Discussionmentioning
confidence: 97%
“…Several genomic surveillance initiatives have been carried out in the last few years to build knowledge regarding the genetic diversity and transmission dynamics of arboviruses in Brazil [5][6][7][8][9][10][11] . Genomic sequencing has revealed that the first case of chikungunya fever (CHIKF) reported in Brazil was an infection by the Asian lineage introduced in a northern state in 2014, while another case reported seven days later in a north-eastern state represented the first known introduction of the East-Central-South-African (ECSA) lineage in the country 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…albopictus are widely distributed (15), autochthonous CHIKF cases caused by the Asian and ECSA genotypes were first detected in December 2013 and September 2014, respectively (16). Subsequent genomic investigations indicated the predominance of the ECSA genotype across Brazil's five geographic regions (17)(18)(19)(20)(21). Currently, Brazil has the highest number of CHIKF cases in the Americas (22).…”
Section: Introductionmentioning
confidence: 99%